(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The rapid evolution of financial technology has revolutionized traditional banking operation, particularly in loan sanctioning and recovery. This paper examines the transformative impact of FINTECH innovation, including AI Based Credit scoring, peer to peer lending, block chain technology, and Machine learning and digital document verification. Additionally, data for this study were gathered through interviews with bank Managers and Officers. Finding of the study highlight that digital lending platform have significant accelerated loan approval process, and enhanced the accuracy of credit risk assessments. Furthermore, for loan recovery automated reminders, communication channels and predictive analytics have improved collection rates and minimized defaults. However, challenges remain including cybersecurity threats, regulatory uncertainties and borrower data privacy concern.